Chemogenetic silencing reveals presynaptic Gi/o protein-mediated inhibition of developing hippocampal synchrony in vivo - Jürgen Graf; Arash Samiee; Tom Flossmann; Knut Holthoff; Knut Kirmse (iScience, 2024)
Summary: Recent advances in understanding how neuronal activity shapes developing brain circuits increasingly rely on Gi/o-dependent inhibitory chemogenetic tools (Gi-DREADDs). However, their mechanisms of action and efficacy in neurons with immature Gi/o signaling are elusive. Here, we express the Gi-DREADD hM4Di in glutamatergic telencephalic neurons and analyze its impact on CA1 pyramidal neurons in neonatal mice. Using acousto-optic two-photon Ca2+ imaging, we report that activation of hM4Di leads to a complete arrest of spontaneous synchrony in CA1 in vitro. We demonstrate that hM4Di does not cause somatic hyperpolarization or shunting but rather mediates presynaptic silencing of glutamatergic neurotransmission. In vivo, inhibition through hM4Di potently suppresses early sharp waves (eSPWs) and discontinuous oscillatory network activity in CA1 of head-fixed mice before eye opening. Our findings provide insights into the role of Gi/o signaling in synchronized activity in the neonatal hippocampus and bear relevance for applying chemogenetic silencing at early developmental stages.